Mercury metalloproteomic profile in muscle tissue of Arapaima gigas from the Brazilian Amazon - Bataglioli, Izabela da Cunha [UNESP]; Queiroz, João Vitor de [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Cavalline, Nubya Gonçalves [UNESP]; Braga, Camila Pereira; Buzalaf, Marília Afonso Rabelo; Zara, Luís Fabrício; Adamec, Jiri; Padilha, Pedro de Magalhães[UNESP] (Springer Nature, 2022)
Metalloproteomics is an innovative methodology for identifying of protein-associated mercury. Thus, we analyzed the muscle proteome of Arapaima gigas (pirarucu), collected in the Madeira River of the Brazilian Amazon, to identify protein-associated mercury, with the aim of identifying possible mercury biomarkers in fish muscle tissue. After obtaining the protein pellet, we conducted two-dimensional electrophoresis (2D PAGE) to fractionate the muscle proteome. Total mercury in muscle tissue and protein pellets and mapping of mercury content in protein spots of the 2D PAGE gels was determined using graphite furnace atomic absorption spectrometry (GFAAS). The protein-associated mercury identification was performed using liquid chromatography coupled with sequence mass spectrometry (LC‒MS/MS). Total mercury determinations by GFAAS indicated concentrations on the order of 153 ± 1.90 mg kg−1 and 142 ± 1.50 mg kg−1 (total precipitation of protein fraction) and 139 ± 1.45 mg kg−1 (fractional precipitation of protein fraction) in muscle tissue and protein pellets, respectively. Mercury concentrations in the range of 48 ± 0.90 to 165 ± 3.00 mg kg−1 were found in twelve protein spots. Among the 2D PAGE protein spots, eleven Hg-binding proteins were identified using LC‒MS/MS, which showed characteristics of mercury exposure biomarkers for important metabolic functions, such as five parvalbumin isoforms, triosephosphate isomerase, cofilin 2 (muscle), and fructose-bisphosphate aldolases.
Keywords: Amazon fish; Hg-binding proteins; Mercury; Mercury metallomics study